The Effect of Technological Capability, Social Capital, and Entrepreneurial Orientation On Firm Performance Through Absorptive Capacityin The Food And Beverage Packaging Industry - Arif Darmawan; Hamdy Hadi; Agustinus Sri Wahyudi (Eduvest - Journal of Universal Studies, 2023)
The purpose of this study is to present a model that describes the general influence of technological capability, social capital, entrepreneurial orientation on firm performance through absorptive capacity in the food and beverage packaging industry in Indonesia which is tested with a structural equation model by processing data from 168 respondents. This study found that technological capability, social capital and absorptive capacity have a positive and significant effect on firm performance. Meanwhile entrepreneurial orientation has a positive but not significant effect on firm performance. Absorptive capacity partially mediates the relationship between technological capability and social capital on firm performance and absorptive capacity fully mediates the relationship between entrepreneurial orientation on firm performance